HUBUNGAN CARA BELAJAR DAN KREATIVITAS TERHADAP HASIL BELAJAR SISWA MATA DIKLAT ELEKTRONIKA LANJUTAN KELAS X TEKNIK AUDIO VIDEO DI SMKN 1 KOTO XI TARUSAN - Nobel Firnando; Sukaya Sukaya; Thamrin Thamrin (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2016)
The aim of this research is to reveal the influenceof learning method and creativity, individually or in groups, to learning outcomes. The population is 49 people and the sample is 34 students of class X TAV in SMK N 1 Koto XI Tarusan. This research is using Simple Random Sampling method. The data ofstudent’s learning outcomes obtained from teachers of Elektronika Lanjutan subject. The data of learning method and creativity the way collected through a questionnaire to students by using a Likert scale that has been tested for validity and reliability. The result showed that (1) learning methodis significantly affecting the learning outcomes of students at19.82%, (2) creativity issignificantly affecting the learning outcomes of students at 14,44%, (3) both learning method and creativity are significantly affecting student’s learning outcomes at 24.05%. The conclusion is learning method and creativity are affecting the student’s learning outcomes at SMK 1 Koto XI Tarusan. The better learning method and creativity, the higher student’s learning outcomes. Keywords: How Learning, Creativity, Learning Outcomes.